Paper crafts : helping children learn (viva education) - Moore, Jo Ellen (Viva Education New Delhi, 2010)
Paper crafts engage children in hands-on learning, enhancing creativity and fine motor skills. Through playful activities, they develop critical thinking and problem-solving abilities while having fun.